3D Printing of Highly Stretchable Strain Sensors Based on Carbon Nanotube Nanocomposites. Issue 10 (31st July 2018) - Abshirini, Mohammad; Charara, Mohammad; Liu, Yingtao; Saha, Mrinal; Altan, M. Cengiz
Abstract : This paper presents the additive manufacturing of a stretchable and electrically conductive polydimethylsiloxane (PDMS) nanocomposite for strain sensing. A long, thin PDMS strip in a zig‐zag pattern of five parallel lines is 3D printed on elastomer substrate using an in‐house modified 3D printer. Multi‐walled carbon nanotubes (MWCNTs) are uniformly deposited on the uncured PDMS lines and cured in an oven. An additional layer of PDMS is then applied on top of MWCNTs to form a thin protective coating. The 3D printed PDMS/MWCNT nanocomposites are characterized using a scanning electron microscope (SEM) to validate the thickness, uniformity, and microstructural features of the sensor cross‐section. The strain sensing capability of the nanocomposites is investigated under tensile cyclic loading at different strain rates and maximum strains. Long‐term performance is tested under cyclic tensile loads for 300 cycles. Sensing experiments indicate that under cyclic loading, the changes in piezo resistivity mimic the changes in the applied load and the measured material strain with high fidelity. In situ micro‐mechanical testing in SEM is carried to investigate the piezoresistive sensing mechanism. Due to the high flexibility of PDMS, the 3D printed sensors are tested to monitor the bending of a human wrist joint as a wearable sensor. Abstract : 3D printed nanocomposite strain sensors provide great potential as flexible and wearable sensors. Additive manufacturing of carbon nanotubes and elastomer based nanocomposites are employed for sensor fabrication. Long‐term sensor performance are characterized under tensile load. Piezoresistive sensing mechanism are experimentally characterized using integrated micro‐mechanical testing system in scanning electron microscope. Fabricated sensors are used as wearable sensors to monitor human wrist motions.